2021
DOI: 10.1002/1878-0261.13077
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts educate normal fibroblasts to facilitate cancer cell spreading and T‐cell suppression

Abstract: In some tumors, a small number of cancer cells are scattered in a large fibrotic stroma. Here, we demonstrate a novel mechanism for expansion of pro-tumor fibroblasts via cancer-associated fibroblast (CAF)-mediated education of normal fibroblasts (NFs). When NFs were incubated with conditioned medium from CAFs, the resulting CAF-educated fibroblasts (CEFs) generated reactive oxygen species (ROS), which induced NF-B-mediated expression of inflammatory cytokines and the extracellular matrix protein asporin (ASP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…We found that CAF‐conditioned media (CM), as well as a mixture of NFs and CAFs in mice xenografts, activated NFs via ROS‐induced activation of nuclear factor NF‐κB signaling, resulting in the generation of CEFs, which secreted pro‐inflammatory cytokines, such as IL‐1β, IL‐6, CXCL‐1, and CXCL‐6, as well as ASPN 26 . ASPN further activated IGF‐I signaling and the tryptophan metabolic pathway, leading to T‐cell cytotoxicity.…”
Section: Role Of Aspn In Caf Biology and Cancer Progressionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that CAF‐conditioned media (CM), as well as a mixture of NFs and CAFs in mice xenografts, activated NFs via ROS‐induced activation of nuclear factor NF‐κB signaling, resulting in the generation of CEFs, which secreted pro‐inflammatory cytokines, such as IL‐1β, IL‐6, CXCL‐1, and CXCL‐6, as well as ASPN 26 . ASPN further activated IGF‐I signaling and the tryptophan metabolic pathway, leading to T‐cell cytotoxicity.…”
Section: Role Of Aspn In Caf Biology and Cancer Progressionmentioning
confidence: 99%
“…ASPN further activated IGF‐I signaling and the tryptophan metabolic pathway, leading to T‐cell cytotoxicity. Inflammatory cytokines, ASPN, and downstream molecules were successively transmitted from fibroblast to fibroblast, ultimately resulting in cancer cell spreading and tumor dissemination 26 …”
Section: Role Of Aspn In Caf Biology and Cancer Progressionmentioning
confidence: 99%
See 3 more Smart Citations